Family Counseling as An Effort to Maintain the Harmony of A Husband Couple Which does not Have Children - Harahap, Erlina; Pardede, Nurhasanah; Astusti, Ira Widi (Universitas Mercu Buana Yogyakarta, 2020)
Every household must have a problem every marriage would want the birth of a child, because children can be trusted with a child's home life will be stronger and more harmonious. Therefore couples who are married try to have children because children are seen as important in the family. The value of children for family or parents in everyday life can be known, among others, from the fact that the child is a place where parents express love, children are a source of family happiness, children are often taken into consideration by a husband and wife to cancel the desire to divorce and also where parents depend various hopes. The purpose of this research is to describe psychological problems, life dynamics and the efforts made in maintaining family harmony without the presence of children. The research method uses a qualitative approach with a descriptive design while the research informants are taken by purposive sampling. The results of research on psychological problems found the fact the presence of a child is not the main factor of family harmony but there are still many other factors. Some of the efforts that a husband and wife can make in maintaining family integrity, the first is cooperation, the second is trying to please the couple, the third is adoption, the fourth is getting closer to religious activities. The benefitsÂ the results of this study are as a basis for implementing family counseling in handling family problems, especially family problems that do not have children.Â